Removal of cadmium ion from aqueous solution using plant-based anionic surfactant impregnated activated carbon / Noor Era Fazirah Jundam, Normadyzah Ahmad and Siti Wahidah Puasa - Jundam, Noor Era Fazirah; Ahmad, Normadyzah; Puasa, Siti Wahidah (Universiti Teknologi MARA Shah Alam, 2020)
Activated carbon was modified by impregnating it with sodium lauryl sulfoacetate (SLSA), a plant-based anionic surfactant and tested to determine whether the surfactant will increase the effectiveness of cadmium ion removal from aqueous solution of cadmium chloride (CdCl2) by activated carbon. The activated carbon used was industrial grade granular type tested without grinding or sieving. The surfactant preparation and the impregnation were done at 600 °C. The heavy metal removal test conducted at 300 °C to mimic normal weather temperature of Malaysia. The granular activated carbon was characterized using BET (Brunauer-Emmet-Teller) while the surfactant chemical properties analysed using FTIR. The aqueous solutions before and after the test were analysed using AAS (atomic absorption spectroscopy). The result obtained has shown that SIAC at 125 ppm has the highest cadmium removal averaging 37.87%. The lowest removal shown by SIAC at 10 ppm with an average of 7.70%.